Behavioral genetic study of self-assessed intelligence - Bratko, Denis; Chamorro-Premuzic, Tomas; Von Stumm, Sophie; Butković, Ana; Vukasović, Tena (2012)
Self-perceived abilities (SPA), which play an important role in academic achievement, have been recently reported to be fully attributable to genetic and non-shared environmental influences. The aim of this study was to explore the genetic and environmental influences on self-assessed intelligence and its relationship with personality and measured IQ. Data on cognitive ability, self-assessed intelligence (SAI), and Five-Factor Model personality traits were collected from 732 Croatian twins (15-22 years old). The results replicated the finding that individual differences in SAI can be attributed to genetic and non-shared environmental influences. Bivariate and multivariate genetic analyses showed intelligence, SAI measures, and personality traits are inter-correlated not only at the phenotypic but also at the genotypic level. Multivariate analyses indicate that around 20% of IQ variance could be explained by SAI and personality traits (Neuroticism, Extraversion, Openness).
Projekt MZOS
ENG